Inhibition of a-amylase and a-glucosidase activities in vitro by extracts of selected medicinal plants (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pant DR, Aryal B, Pun D, Sharma S, Joshi GP. 2021. Inhibition of a-amylase and a-glucosidase activities in vitro by extracts of selected medicinal plants. Biodiversitas 22: 1187-1193. Several medicinal plants are being used traditionally in the treatment/management of Diabetes Mellitus (DM). The present work focuses on experimental verification of antidiabetic potential of different medicinal plants that have been reported to be used traditionally to manage DM. Aqueous and methanolic extracts of 12 species of plants were studied for their inhibitory effect on the activities of a-amylase and a-glucosidase, two key enzymes of carbohydrate metabolism. The extracts of all the species showed very high degree (nearly 90% or above) of inhibition of ?-amylase irrespective of the extraction solvent. The aqueous extracts of Asterella wallichiana, however, showed only 63.60% inhibition of a-amylase. Except for Asterella wallichiana, the percentage inhibition of a-amylase in aqueous and methanolic solution in all the species tested were almost similar. The percentage inhibition of a-glucosidase was lower than that of a-amylase for all the species in both types of extraction medium. The highest percentage inhibition of a-glucosidase (81.13±1.36 %) was found in methanolic extracts of Rhuschinensis. The inhibition of a-glucosidase was much higher in methanolic extracts than in aqueous extracts for all the species tested. High degree of inhibition of a-amylase activity in vitro by the extracts of all the species tested provides scientific basis for using these plants in the management/treatment of diabetes in traditional medicine.
Keywords: a-amylase, a-glucosidase, diabetes, medicinal plants, methanolic extracts